2008
DOI: 10.1177/0145445508320927
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Construct Validity of Dixon and Johnson's (2007) Gambling Functional Assessment

Abstract: The Gambling Functional Assessment (GFA; Dixon & Johnson, 2007) is a 20-item self-report inventory identifying four potential consequences maintaining gambling behavior. Exploratory and confirmatory factor analyses are performed for two large, nonclinical samples of university undergraduates. For the exploratory analysis, the optimal model yields two factors: Positive Reinforcement (correlated with GFA Sensory, Attention, and Tangible scores) and Negative Reinforcement (correlated with GFA Escape scores). One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 16 publications
3
24
1
Order By: Relevance
“…The lowest observed Cronbach's alpha was 0.87. These results were superior to those reported for the original GFA (see Miller et al 2009a). Furthermore, to put these results in perspective, internal consistency measures for the SOGS have ranged from 0.69 (Stinchfield 2002) to 0.97 (Lesieur and Blume 1987).…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…The lowest observed Cronbach's alpha was 0.87. These results were superior to those reported for the original GFA (see Miller et al 2009a). Furthermore, to put these results in perspective, internal consistency measures for the SOGS have ranged from 0.69 (Stinchfield 2002) to 0.97 (Lesieur and Blume 1987).…”
Section: Discussionmentioning
confidence: 71%
“…With a 4-week interim between administrations, the lowest observed correlation coefficient was 0.74, which was for the scores on the positive reinforcement items after the ''non-gamblers'' had been excluded from the analysis. Miller et al (2009a) did not test the reliability of the original GFA at 4 weeks, so one cannot conclude whether the GFA-R performed better or worse than the GFA over this time interval. However, over this same time interval, SOGS scores correlated at 0.89 or higher, which was superior to the GFA-R. Millon et al (1997) reported that test-retest reliability of MCMI-III ranged between 0.82 and 0.91 over 5-14 days with a similarly sized sample.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations